PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN REPUTASI PERUSAHAAN DAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI - Jao, Robert; Randa, Fransiskus; Holly, Anthony; Laorens, Evelyn (Universitas Muhammadiyah Palembang, 2024)
This study aims to analyze the effect of corporate social responsibility on firm value, with company reputation and financial performance as mediating variables. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020-2022. The number of samples is 37 company data for three years, which were selected using purposive sampling. The study results found that corporate social responsibility positively and significantly affects a corporate reputation. Corporate social responsibility has a positive and significant impact on financial performance. Company reputation has a positive but insignificant effect on firm value. Financial performance has a positive and significant impact on firm value. Corporate social responsibility has a positive but insignificant effect on firm value. Corporate reputation cannot mediate the impact of corporate social responsibility on firm value. Financial performance can mediate corporate social responsibility's impact on firm value.